Ethical and legal aspects of the legalization of marijuana and other soft drugs - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2017)
The main purpose of this article is to present the most important ethical and legal aspects of the legalization of marijuana and other soft drugs. The dispute over the legalization of access to the usage of drugs is an elevation to the point of moral revolution, which is currently engaged on a global scale. Over the past decade, there has been a strong shift in public opinion in many countries in favor of drug policy reform. Arguments about the prohibition of drugs and over drug policy reform are subjects of considerable controversy. The problem of legal access to drugs is a very complex interdisciplinary issue that requires a reliable diagnosis on the borderline of ethics, medicine, philosophy, law, sociology, and political philosophy. The ethical evaluation of the usage of drugs and distribution should always precede the adoption of specific measures of a legal nature.